Communication models : for the study of mass communications - McQuail, Denis; Windahl, Swen, 1942- (London ; New York : Longman, 1999)
Presents the main existing models of the mass communications process which have been developed during the last thirty years, providing brief descriptions of the most significant concepts and ideas in the study of mass communication, using graphic and verbal models
-- 1. Introduction --- 2. Basic Models --- 3. Personal Influence, Diffusion and Short-Term Effects of Mass Communication on Individuals --- 4. Effects of Mass Communication on Culture and Society --- 5. Audience-Centred Models --- 6. Media Organisation, Selection and Production --- 7. Planned Communication --- 8. New Media and The Information Society --- 9. International Communication
Includes bibliographical references and index
Keywords: Communication models; Mass media; Mass media -- Study and teaching